2020
DOI: 10.1111/os.12860
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Meniscal Ramp Lesion Without Obvious Anterior Cruicate Ligament Rupture

Abstract: Objectives: The purpose of the present paper was to study isolated meniscal ramp lesions without obvious ACL rupture. Their biomechanical mechanisms were analyzed and their clinical characteristics were reviewed. The clinical effects of an all-inside horizontal mattress suture for isolated ramp lesions were evaluated. Materials and Methods: Twenty isolated meniscal ramp lesion patients without obvious ACL rupture from 2015 to 2017 were retrospectively reviewed. Preoperative MRI showed intact ACL and signs of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…The authors also reported a mean postoperative VAS score of 2.1 ± 1.4 and a mean Lysholm score of 85.7 ± 3.5 at the second-year follow-up. 18 In our study, where the mean follow-up period was 37.6 months, the mean VAS score was 2.34 ± 2.9, the Lysholm score was 85.37 ± 14.01, and the mean IKDC score was 85.32 ± 8.78. These results are in accordance with those of Jiang et al 18 .…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…The authors also reported a mean postoperative VAS score of 2.1 ± 1.4 and a mean Lysholm score of 85.7 ± 3.5 at the second-year follow-up. 18 In our study, where the mean follow-up period was 37.6 months, the mean VAS score was 2.34 ± 2.9, the Lysholm score was 85.37 ± 14.01, and the mean IKDC score was 85.32 ± 8.78. These results are in accordance with those of Jiang et al 18 .…”
Section: Discussionmentioning
confidence: 47%
“… 18 In our study, where the mean follow-up period was 37.6 months, the mean VAS score was 2.34 ± 2.9, the Lysholm score was 85.37 ± 14.01, and the mean IKDC score was 85.32 ± 8.78. These results are in accordance with those of Jiang et al 18 . Although the authors did not mention the tear types and their treatment approach in their study, they reported that outcomes were perfect.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“… 12 , 13 Notably, isolated MRL may exist even in the absence of obvious ACL rupture, possibly as a sequalae of ACL longitudinal splits or degeneration. 14 MRL is also seen alongside root, horizontal and other types of medial meniscal tears. 15 However, the true incidence of MRL is unknown due to the high rate of mis or underdiagnosis resulting from low sensitivity of imaging modalities, 16 poor intra-operative visualization and surgical skills.…”
Section: Overview Of Ramp Lesion Of the Medial Meniscusmentioning
confidence: 98%